Association between metformin use and progression of monoclonal gammopathy of undetermined significance to multiple myeloma in US veterans with diabetes mellitus: a population-based retrospective cohort study. Issue 1 (January 2015) - Chang, Su-Hsin; Luo, Suhong; O'Brian, Katiuscia K; Thomas, Theodore S; Colditz, Graham A; Carlsson, Nils P; Carson, Kenneth R
Summary: Background: Multiple myeloma is one of the most common haematological malignancies in the USA and is consistently preceded by monoclonal gammopathy of undetermined significance (MGUS). We aimed to assess the association between metformin use and progression of MGUS to multiple myeloma. Methods: We did a retrospective cohort study of patients registered in the US Veterans Health Administration database and diagnosed with MGUS between Oct 1, 1999, and Dec 31, 2009. We included patients (aged >18 years) with at least one International Classification of Diseases (9th revision) code for diabetes mellitus and one treatment for their diabetes before MGUS diagnosis. We reviewed patient-level clinical data to verify diagnoses and extract any available data for size of baseline M-protein and type of MGUS. We defined metformin users as patients with diabetes who were given metformin consistently for 4 years after their diabetes diagnosis and before multiple myeloma development, death, or censorship. Our primary outcome was time from MGUS diagnosis to multiple myeloma diagnosis. We used Kaplan-Meier curves and Cox models to analyse the association between metformin use and MGUS progression. Findings: We obtained data for 3287 patients, of whom 2003 (61%) were included in the final analytical cohort. Median follow-up was 69 months (IQR 49–96). 463 (23%) participants were metformin users and 1540 (77%) participants were non-users. 13 (3%) metformin users progressed to multiple myeloma compared with 74 (5%) non-users. After adjustment, metformin use was associated with a reduced risk of progression to multiple myeloma (hazard ratio 0·47, 95% CI 0·25–0·87). Interpretation: For patients with diabetes diagnosed with MGUS, metformin use for 4 years or longer was associated with a reduced risk of progression of MGUS to multiple myeloma. Prospective studies are needed to establish whether this association is causal and whether these results can be extrapolated to non-diabetic individuals. Funding: Barnes-Jewish Hospital Foundation, National Institutes of Health, Agency for Healthcare Research and Quality, American Cancer Society.